Organizational Justice and Innovative Work Behavior: Mediating Role of Knowledge Sharing - Nerizza Afrida Putri Anasya; Suhana, Suhana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study analyzes how knowledge sharing mediates the relationship between organizational justice and innovative work behavior. The object of research is the Semarang City Regional Revenue Agency. The population of this research is all ASN employees of Semarang City Regional Revenue Agency, sampling technique using census sampling method that is using the entire population to be sampled. The type of data used is primary data obtained directly through distributing questionnaires. The analysis in this study used the Structural Equation Model (SEM) method with the help of SmartPLS 4 software. The results of this study indicate that knowledge sharing partially mediates the relationship between organizational justice and innovative work behavior. Organizational justice has a significant positive effect on innovative work behavior and knowledge sharing, and knowledge sharing has a significant positive impact on innovative work behavior. The study has theoretical and practical implications. Through innovative work behavior, employees of the Semarang City Regional Revenue Agency can improve service quality and help the organization achieve its goals.